Considering risk associated with leisure time physical activity (LTPA) at craft breweries: overlooking dangers in the name of fun - Alana N Seaman; Lindsey Schroeder; Madison Peace; Michele Abee; Laura Morris (Research in Hospitality Management)
Many breweries in the US have become popular settings for leisure time physical activity (LTPA). While risk is widely accepted as an inherent part of sport and physical activity (PA), breweries are places of increased risk due to the nature of their hospitality- and beer production-focused environments. Utilising a multi-case study methodology, this study sought to explore how physical risk is conceptualised relative to LTPA at these venues. Data revealed that engagement in LTPA at breweries was viewed as sport and thus physical risk was considered a part of that; most participants and management seemed oblivious to the increased risk in the settings; that there was a little concern for or clarity about liability; and a lack of preparedness on site was prevalent. Together the findings suggest the affect heuristic of risk perception may be influencing stakeholders where risk is being overlooked and minimised in the name of fun. Such attitudes contrast sharply with the views of experts, implying the existence of a knowledge deficit about risk in these settings among hosts and patrons alike; a deficit that should be addressed with more explicit information and clarity about hazards, potential for accidents and liability associated with LTPA at breweries.